FROM CONVENTIONAL TO SUSTAINABLE MOBILITY: EXAMINING BYD ELECTRIC VEHICLE PURCHASE INTENTION AMONG INTERNAL COMBUSTION ENGINE VEHICLE OWNERS IN SURABAYA - Hananiel Gunawan; Priskilla E.E. Napitupulu; Janice Carysa Siahaya (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The global transition from conventional mobility to sustainable mobility is driving the accelerated adoption of electric vehicles (EVs), particularly in emerging markets. This study aims to analyze the factors influencing the purchase intention of BYD electric vehicles among the internal combustion engine (ICE) vehicle owners in Surabaya. The ICE vehicle owners are seen as a potential segment in the transition to sustainable mobility. This study examines the influence of environmental concern, brand credibility, perceived benefits, and competitive advantage on purchase intention. Environmental concern reflects an individual's level of concern for environmental issues, while brand credibility is positioned as an intangible strategic asset that builds consumer trust. Perceived benefit describes consumers' perceptions of the functional, economic, and environmental benefits of electric vehicles, while competitive advantage represents the perception of BYD's strategic superiority over conventional vehicles. Data will be collected through a structured questionnaire distributed to internal combustion engine vehicle owners in Surabaya. Data analysis was conducted using Structural Equation Modeling (SEM) to simultaneously examine the relationships between variables. The results of this study are expected to contribute to the development of strategic management and sustainable marketing literature, particularly in understanding the determinants of consumer transition to electric vehicles. Practically, the findings of this study can serve as a basis for electric vehicle manufacturers in formulating effective sustainable positioning strategies in the Indonesian urban market.